Model Investigation of a Low Froude number Roller Bucket at Urriðafoss HEP - Gísli Steinn Pétursson 1987- (2013)
Evaluation of the performance of a low head, low Froude number slotted roller bucket was conducted using a 1:40 Froude-scaled physical model. The roller bucket structure is part of the proposed design for the Urriðafoss hydroelectric power plant in the Lower Þjórsá area in southern Iceland. Four bucket invert elevations were tested for a range of operational conditions for evaluation of the performance of the roller bucket and the downstream channel. The data from the physical model was compared to a previous study on roller buckets to support the design guidelines available. Sectional and 3D numerical models were made in ANSYS-CFX with a standard k-e turbulence model. The numerical results were compared to water elevations, visual observations and velocity, measured by an Acoustic Doppler Velocimeter (ADV), from the physical model. The numerical model was then used to interpolate the data from the physical model in order to optimize the bucket invert elevation. The results show that for the buckets tested the performance of the structure improves with decreasing elevation. The flow characteristics in the downstream channel suggest that the bucket radius is below minimum for the proposed final design, this is supported by extrapolation of the design graphs. The physical model and the 3D numerical models are in good agreement while the 2.5D model is unable to simulate the behaviour of the system due to the complexity of the system layout. The data from the physical model shows good correlation to the previous study and supports the extrapolation of the previous data set. Virkni veltuþróar með lága orkuhæð og Froude tölu var metin í straumlíkani í kvarðanum 1:40. Veltuþróin er hluti af fyrirhugaðri Urriðafoss virkjun í Neðri-Þjórsá. Fjórar hæðir á botni veltuþróarinnar voru prófaðar við mismunandi rekstrarskilyrði þar sem virkni flóðamannvirkja var metin. Mæld gögn úr straumlíkaninu voru borin saman við eldri rannsókn til að styrkja þær hönnunar forsendur sem notast er við. Sneiðlíkön og þrívíð töluleg líkön ...